Tick-borne Wuhan mivirus and Lihan tick virus in Rhipicephalus microplus in Guizhou Province, China - Jixia Tang; Qiu Chen; Jiao Meng; Shenchun Wu; Chaomin Zhou; Yisong Dai; Xingxing Chen; Jiafu Jiang; Sun Yi; Wuchun Cao; Fuxun Yu; Jiahong Wu; et al. (Asian Pacific Journal of Tropical Medicine)
Objective: To uncover the characteristics of tick-borne viruses in Guizhou Province. Methods: A total of 414 Rhipicephalus microplus were collected from 5 counties in Guizhou Province, China from August 2022 to October 2023. A group of 12 ticks from each study sites was sequenced by next generation sequencing. Results: 8 contigs of Wuhan mivirus (Chuviridae, Mivirus) with the length of 2094 bp to 11 580 bp and 4 contigs of Lihan tick virus (Phenuiviridae, Uukuvirus) with the length of 1 401 bp to 7 080 bp were obtained, respectively. The prevalence rate of Wuhan mivirus and Lihan tick virus was 51.98% and 11.30%, respectively. The identities of gene sequences of both Wuhan mivirus and Lihan tick virus were 94%-100% compared with sequences in the National Center for Biotechnology Information. The phylogenetic analysis indicated that the Wuhan mivirus detected in this study was in the same branch with the Wuhan mivirus of Sichuan isolate TIGMIC-27 (NCBI Accession: OP628598) and Zhejiang isolate TIGMIC-45 (NCBI Accession: OP628613). In addition, the Lihan tick virus was in the same branch with the Sichuan Lihan tick virus isolate TIGMIC-46 (NCBI Accession: ON812358). Conclusions: Both Wuhan mivirus and Lihan tick virus were prevalent in Rhipicephalus microplus in Guizhou Province. More studies are needed to understand the pathogenicity and public health threats of these tick-borne viruses.